2016
DOI: 10.1186/s41182-016-0038-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, seasonal variation, and antibiotic resistance pattern of enteric bacterial pathogens among hospitalized diarrheic children in suburban regions of central Kenya

Abstract: BackgroundThe epidemiology of enteric pathogens has not been well studied in Kenya because of wide disparities in health status across the country. Therefore, the present study describes the prevalence of enteropathogenic bacteria, their seasonal variation, and antibiotic resistance profiles among hospitalized diarrheic children in a suburban region of central Kenya.MethodsFecal samples were collected between July 2009 and December 2013 from a total of 1410 children younger than 5 years, hospitalized with acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
35
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 29 publications
15
35
4
3
Order By: Relevance
“…The overall prevalence of Shigella and Salmonella isolated in this study was 8.0% [4.6-11.4%] which is lower than compared with studies conducted in Tanzania A single S. Typhi 0.4% 95% CI [0-1.1%] was isolated in this study which is in line with the ndings reported from the same country in Addis Ababa, 0% (31), 1.1% (43), in contrast to our nding higher rates was reported from Sudan 4.0% (40), China 4.3% (27), Addis Ababa, Ethiopia 3.95% (26), Kenya 3.4% (46), Turkey 3% (47), Gondar 1.6% (48), and Hawassa 1.5% (24). This difference might be due to sampling size, weather condition and study subjects age differences.…”
Section: Discussionsupporting
confidence: 91%
“…The overall prevalence of Shigella and Salmonella isolated in this study was 8.0% [4.6-11.4%] which is lower than compared with studies conducted in Tanzania A single S. Typhi 0.4% 95% CI [0-1.1%] was isolated in this study which is in line with the ndings reported from the same country in Addis Ababa, 0% (31), 1.1% (43), in contrast to our nding higher rates was reported from Sudan 4.0% (40), China 4.3% (27), Addis Ababa, Ethiopia 3.95% (26), Kenya 3.4% (46), Turkey 3% (47), Gondar 1.6% (48), and Hawassa 1.5% (24). This difference might be due to sampling size, weather condition and study subjects age differences.…”
Section: Discussionsupporting
confidence: 91%
“…The high AMR frequencies for first-line drugs, in particular penicillins, detected in this study are similar to reports of other intestinal, extra-intestinal and environmental isolates of E. coli 22,37 . Of note, the high levels of ciprofloxacin-resistance found in this study at the Asian sites corresponded to high levels reported in clinical cases in India, Bangladesh and Pakistan 17,18,21,23,24,38 .…”
Section: Discussionsupporting
confidence: 89%
“…Of greatest concern are multi-drug resistant (MDR) E. coli (non-susceptible to one or more agents in at least three antimicrobial categories) 16 , particularly those that are fluoroquinolone resistant and/or produce extended-spectrum beta-lactamases (ESBL). While several recent studies have reported increases in ESBLs 17,18 , gentamicin 19,20 , ciprofloxacin [20][21][22][23][24] and revealed diverse AMR profiles, these data have largely come from E. coli responsible for disease in hospital settings. Thus, there remain significant gaps in knowledge of the prevalence of AMR in human intestinal E. coli populations globally, particularly in the developing nations of sub-Saharan Africa and South Asia 25 .…”
Section: Introductionmentioning
confidence: 99%
“…This was also the case for the ETEC and EAEC pathotypes, but a 382 reverse pattern was observed for STEC and EPEC, in a way that their prevalence was slightly 383 lower during warmer seasons than cooler seasons. These results are in line with previous 384 studies in Mexico (41) and Kenya (42 sampling proportion of 1:2 for provinces. We also sampled provinces in a way that an even 396 distribution of sampled provinces is reached throughout the country.…”
supporting
confidence: 93%